Analisis protein dan kualitas organoleptik nugget ikan lemuru (Sardhella Lemuruu) - Amalia Amalia; Andriani Andriani (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: Processing meat from lemuru fish into nuggets is one of the uses of the art of utilizing fish products that have low economic value into high ones, besides that, the most important thing is the high nutritional content and quality which is the main attraction for this product.Objective: The aim of the study was to determine the effect of adding lemuru on organoleptic properties and protein content.Methods: The study used an experimental method with a Non-Vactorial Completely Randomized Design (CRD) with 3 treatments and 3 repetitions. The lemuru fish nuggets were then tested for organoleptic (taste, color, aroma, texture) in the nutrition laboratory and analyzed for protein content at Goods Quality Testing and Certification Center of Aceh. Statistical analysis using one-way Anova test.Results: Statistical results have shown that there is no significant effect on the addition of 150 gr, 200 gr, and 250 gr lemuru fish on the color of the nuggets (p value > 0.05), but a significant effect on the texture with the addition of 250 gr fish with an average value of 4.10 (like ), taste with the addition of 250 g of fish with an average value of 4.47 (likes) and aroma with the addition of 250 g of fish with an average value of 4.00 (likes) with a p value of < 0.05. Furthermore, the protein test had no significant effect with the addition of 150 gr, 200 gr, 250 gr lemuru fish (p= 0.123).Conclusion: The addition of lemuru fish had a significant effect on the texture, taste, and aroma of the nuggets, the results of the chemical test of protein content did not significantly affect the protein content of the nuggets.